IMPLEMENTATION OF NANJING SWANSOFT-BASED CNC MILLING SIMULATION IN THE MANUFACTURE OF UMSB BRAND GRAVIS PRODUCT - Leni, Desmarita; Muchlisinalahuddin, Muchlisinalahuddin; Usni, Eka Nur; Peng, Lim Hooi; Fadel, Habib Putra (International Journal of Multidisciplinary Research and Literature, 2026)
Development of engraved products featuring institutional identity at Mechanical Engineering Department, Universitas Muhammadiyah Sumatera Barat offers promotional opportunities and commercialization potential. Manufacturing plaques, keychains, and name tags through CNC Milling technology demands precision in design formulation, toolpath optimization, and determination of cutting parameters that align with material properties. This research implements Nanjing Swansoft-based CNC Milling simulation for producing UMSB-branded gravis products, analyzing toolpath prediction accuracy, machining duration, and evaluating contributions toward production efficiency. The study applies descriptive-analytical approach with case study method conducted at Faculty of Engineering during November 2025 to January 2026. Research stages encompass comprehensive literature review on CNC milling technology and parameter optimization, two-dimensional and three-dimensional design creation using SolidWorks software for aluminum material sized 240×60×40 mm, G-code programming employing single tool strategy with Ø10mm end mill designated as T01, configuration of FANUC 0i-M controller with G54 work coordinate system, and execution of four machining phases: facing, roughing, semi-finishing, and finishing operations targeting 20 mm engraving depth. Dimensional validation demonstrates accuracy within ±0.1 mm tolerance on critical dimensions with maximum deviation of ±1.5% in engraving zones, maintaining compliance with manufacturing tolerance limits for institutional souvenir applications. Actual simulation cycle time recorded 68 minutes 50 seconds with deviation below 5% from initial programming calculations. Cutting force monitoring revealed optimal range between 90-140 N without collision detection warnings. Surface quality assessment indicates superior finishing profiles with uniform stepover ridge formation and sharp edge definition on UMSB typography elements without excessive burr formation. Integration of CAD-CAM systems through simulation validates feasibility of CNC instructions for actual machine implementation, confirming Nanjing Swansoft simulator effectiveness as cost-efficient tool for programming verification and material waste reduction supporting manufacturing digitalization within Industry 4.0 framework.